Comparative Evaluation of HVT-IBD Vector, Immune Complex, and Live IBD Vaccines against vvIBDV in Commercial Broiler Chickens with High Maternally Derived Antibodies - Sedeik, Mahmoud E. (Animals (Basel), 2019)
SIMPLE SUMMARY: Vaccination is the main method to control infectious bursal disease (IBD) in commercial broilers worldwide. The main obstacle to the vaccination process is maternally derived antibodies; thus, new generations of vaccines such as vector and immune complex vaccines have been developed. The efficacies of new and classical vaccines were compared to those of vvIBDV in the presence of high levels of maternally derived antibodies. The best results were obtained when using the vector IBD vaccine followed by the immune-complex vaccine, and the use of killed along with the live intermediate vaccine in terms of mortality, feed conversion ratio, bursal and spleen index, bursal lesion score, and serology. ABSTRACT: Infectious bursal disease (IBD) causes increased mortality and severe immunosuppression in commercial chickens. Currently, vaccination mainly used to control IBD. In this study, Group A (n = 30) received the HVT-IBD vector vaccine (Vaxxitek(®)) s/c and Group B (n = 30) received the immune complex vaccine (Bursa-Plex(®)) s/c at 1 day of age. Group C (n = 30) received a single dose of intermediate plus vaccine (228E) through the eye-drop route at 14 days of age. Group D (n = 30) was vaccinated twice with the intermediate vaccine (D78) at 12 and 22 days of age by eye-drop. Group E (n = 30) had the same treatment as group D along with the IBD killed vaccine (Nobilis G(®)) at 5 days of age. The PC (n = 20) and NC (n = 20) groups were non IBD vaccinated birds either challenged or not with vvIBDV, respectively; 20 chicks from each group were challenged with vvIBDV at 4 weeks of age. Based on clinical signs, postmortem gross lesions, histopathological changes, mortality rate, feed conversion rate, serology, bursal and spleen indices, the HVT-IBD vector vaccine administered was found to be safer and provided better protection against the vvIBDV challenge. The use of a killed IBD vaccine at an earlier age in broilers strengthened the protection induced by double doses of intermediate vaccines in broilers with high maternally derived antibodies against the vvIBDV challenge.